COMPARATIVE STUDY OF INTEGRATED MULTICRITERIA DECISION MAKING: AHP-TOPSIS VS ENTROPY-TOPSIS FOR PRIORITIZING ROAD DAMAGE REPAIR - Alam Sur, Widiya Astuti; Adriana, Marlia; Machfiroh, Ines Saraswati; Dewi, Norminawati; Kurniawan, Budi; Safitri, Intan (Jurnal Jalan Jembatan, 2025)
This study compares two integrated methods, specifically the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), to determine prioritized road sections for repair. The first method, AHP-TOPSIS, assigns weights to damage criteria based on the characteristics of road damage types. The second method, Entropy-TOPSIS, determines the weights of damage criteria using the Entropy formula. The accuracy of both methods is assessed by comparing their ranking results to the Pavement Condition Index (PCI) assessment based on the percentage of similarity. Based on the accuracy percentages, Entropy-TOPSIS demonstrates higher accuracy (27.5%) compared to AHP-TOPSIS (21.25%). Meanwhile, the road sections prioritized for repair yielded the same ranking results between AHP-TOPSIS and Entropy-TOPSIS, specifically the road sections on Jorong Beach, from STA 3+401 to 3+500 (Alternative 70). The results of this study support the development of more accurate and efficient decision-making models for infrastructure maintenance, which can be applied to broader transportation management systems. Keywords: road damage, PCI, AHP, entropy, TOPSIS